STUDI LITERATUR TENTANG KESULITAN BELAJAR UNDERACHIVER SISWA REMAJA - Adina Sari Pratiwi; Rosmawati Rosmawati; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study was conducted to determine the basic concepts and theories, factors and efforts to overcome underachivers. The type of research used is literature study. The instrument used in this research is a combination of national journals and international journals. Data analysis in this study used qualitative text content analysis. The results showed that underachivers were adolescent students who lacked achievement or had low learning achievement in academics but had a high level of intellectual ability so that there was an expected mismatch between their abilities and learning achievement. And there are also various theories found such as Rimm's Theory, Wellington's Theory, Whitmore's Theory, Gallagher's Theory and Kaufman's Theory. As for the factors that influence, namely internal and external factors that exist in adolescent students. So that efforts can be made by providing group guidance services for modeling techniques, WDEP system techniques, role playing techniques, group counseling services, self-monitoring techniques, classical guidance services, procedures for giving psychoeducation interventions, polycentric teaching methods, mathematical reasoning skills in solving program problems. linear underachiver students, quantum learning, training on independent learning in underachiever students and self-determination approach intervention program.Key Words: Literature Study, Underachiver, teenage students